The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.842693
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomic and Transcriptomic Analyses Reveal Novel Insights of Anthocyanin Biosynthesis on Color Formation in Cassava Tuberous Roots

Abstract: Yellow roots are of higher nutritional quality and better appearance than white roots in cassava, a crucial tropical and subtropical root crop. In this work, two varieties with yellow and white cassava roots were selected to explore the mechanisms of color formation by using comparative metabolome and transcriptome analyses during seven developmental stages. Compared with the white-rooted cassava, anthocyanins, catechin derivatives, coumarin derivatives, and phenolic acids accumulated at higher levels in yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…In this study, 299 SCMs were identified by the non-targeted metabolome in SC and PC. The quantity of SCMs in this study was significantly different from that in previous research into storage roots [ 26 , 27 ], owing to the characteristics of different cassava varieties. The composition and content of metabolites in cassava storage roots can directly affect the quality.…”
Section: Discussioncontrasting
confidence: 96%
“…In this study, 299 SCMs were identified by the non-targeted metabolome in SC and PC. The quantity of SCMs in this study was significantly different from that in previous research into storage roots [ 26 , 27 ], owing to the characteristics of different cassava varieties. The composition and content of metabolites in cassava storage roots can directly affect the quality.…”
Section: Discussioncontrasting
confidence: 96%
“…Anthocyanins are the major colorants of flowers, fruits, buds, and young shoots, as well as of purple and purple-red leaves in autumn (Falcone Ferreyra et al 2012; Kayesh et al 2013; Mekapogu et al 2020; Vaknin et al 2005). Anthocyanins also accumulate and impart a red color to the roots or ARs of herbaceous plants, such as purple carrots, cassava roots, and Raphanus sativus (Chialva et al 2021; Fu et al 2022; Xiao et al 2021), and accumulate in the ARs of the woody plant Metrosideros excelsa (Solangaarachchi and Gould 2001). In this study, chemical assays illustrated that flavonoids, anthocyanins, and carotenoids significantly accumulated in poplar ARs under sunlight exposure (Figure 3C-E), and then, the metabolomic analysis identified the accumulated flavonoids metabolites as flavonols, flavones, and anthocyanins (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Some specific cassava germplasms have purple leaves, which are rich in flavonoids, especially anthocyanin. Recent studies indicated that flavonoids are detected in the leaves or storage roots of cassava (Omar et al, 2012;Xiao et al, 2021;Fu et al, 2022). However, metabolomic and genetic differences in anthocyanin biosynthesis of cassava leaves in those specific germplasms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%